Evidence of a predisposing locus to bipolar disorder on Xq24-q27.1 in an extended Finnish pedigree. - Pekkarinen, P; Terwilliger, J; Bredbacka, P E; Lönnqvist, J; Peltonen, L (Genome Research, 1995)
An X-chromosomal predisposing locus to manic-depressive illness has been suggested since 1969 on the basis of the cosegregation of this trait in some families with phenotypic markers, such as color blindness, the glucose-6-phosphate dehydrogenase deficiency, and the coagulation factor IX deficiency. However, the conclusive evidence and the exact location of the putative X-chromosomal locus have remained controversial. We report here a linkage between DNA markers near the coagulation factor IX gene and bipolar disorder in an extended pedigree rising from the genetically isolated population of Finland. A distinct chromosomal haplotype covering a 20-cM region on Xq24-q27.1 could be demonstrated to segregate with bipolar disorder. These findings should encourage research groups to study extended family materials with Xq24-q27.1 markers to finally resolve the question of the X-chromosomal linkage of bipolar disorder.
10.1101/gr.5.2.105